Modeling of anomalous moisture diffusion in nanographene reinforced thermoset polymers. (April 2015) - Kumar, Abhishek; Roy, Samit
Abstract: This paper aims to study the anomalous two-stage moisture diffusion in baseline thermoset epoxy (EPON 862), and in nanographene platelet (NGP) reinforced epoxy. The deviation from Fickian diffusion is assumed to be intrinsically dependent on the time varying viscoelastic response of the epoxy and its nanoparticle reinforced polymer nanocomposite. A novel viscoelasticity based model has been formulated which aims to capture the response of the two-stage moisture absorption response, incorporating the effect of time-dependent relaxation of the material, and random orientation and aspect ratio of the NGPs on the moisture absorption. Moisture uptake experiments at 60 °C and 90% relative humidity were performed in an environmental chamber for five different weight percentages (wt%) ranging from 0.1% to 3% NGPs and their response was compared with baseline epoxy specimens. Upon benchmarking to extract modeling parameters, the model was used to predict anomalous moisture uptake for 0.1 and 2 wt% NGP. Good agreement between the model prediction and experimental data for benchmark cases was observed.